2017
DOI: 10.2174/1874434601711010014
|View full text |Cite
|
Sign up to set email alerts
|

Family Health Conversations have Positive Outcomes on Families - A Mixed Method Research Study

Abstract: Background:Having a family member living in a residential home affects the entire family and can be hard to handle. Family members require encouraging and open communication support from nurses during and after relocation to a residential home. A Family Systems Nursing intervention, “Family Health Conversations” (FamHC) was conducted in order to strengthen the health of families having relatives at residential home for older people.Objectives:The aims of this study were to evaluate the responses to the Family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 50 publications
(58 reference statements)
1
24
0
Order By: Relevance
“…Also, previous studies have shown that families participating in FamHC have improved insight, understanding and communication. Thus, negative feelings could be expressed openly and reflected upon within the family (17,(31)(32)(33)(34)(35). Also, a study by Sundin et al (36) shows that family members share their beliefs and talk about serious issues.…”
Section: Discussionmentioning
confidence: 99%
“…Also, previous studies have shown that families participating in FamHC have improved insight, understanding and communication. Thus, negative feelings could be expressed openly and reflected upon within the family (17,(31)(32)(33)(34)(35). Also, a study by Sundin et al (36) shows that family members share their beliefs and talk about serious issues.…”
Section: Discussionmentioning
confidence: 99%
“…This is what “working it through” is about, and this study's findings are in total correspondence with the findings reported. Family members cope by using their personal resources and by receiving support from others…”
Section: Discussionmentioning
confidence: 99%
“…This is what "working it through" is about, and this study's findings are in total correspondence with the findings reported. Family members cope by using their personal resources and by receiving support from others [28][29][30] Families participating in the FamHC reported healthier family function than families just having regular follow up. 17 A healthy family function may be facilitated by health professionals supporting the family during the ICU stay while following proper guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are studies with a qualitative approach that demonstrate a positive effect. In these studies, patients have a different diagnosis (Dorell, Isaksson, Östlund, & Sundin, ; Östlund, Bäckström, & Saveman, ). In future studies in the field, it is recommended that the families themselves choose when the therapeutic conversations will take place during the course.…”
Section: Relevance To Clinical Practicementioning
confidence: 99%
“…However, there are studies with a qualitative approach that demonstrate a positive effect. In these studies, patients have a different diagnosis (Dorell, Isaksson, Östlund, & Sundin, 2017;Östlund, Bäckström, & Saveman, 2016).…”
Section: Rele Van Ce To Clini C Al Pr Ac Ti Cementioning
confidence: 99%